An implicit good news in a Javanese indigenous religious poem - Chandra, Robby I. (HTS teologiese studies, 2022)
Contextualising biblical teaching entails the adoption of certain forms, terms or thought patterns that might confuse the original message, especially if the effort takes place in a Javanese culture context that is full of subtlety and indirect communication. This study analyses a Javanese poetry form that contains the narrative of Jesus’ encounter with a Samaritan woman. The indigenous poems are widely sung by the adherents of Javanese indigenous religions. However, only a few studies are conducted on such indigenous poems that contain Christian messages. This study examines whether or not the poetry form and religious terms that the writer used could serve as a vehicle to convey the good news message of the narrative of John 4:4–42 instead of creating impediment. Through literary form analysis followed by content analysis, the results showed that the Javanese poem contains several cantos, each with an embedded meaning. Finally, it intends to demonstrate how a combination, instead of contestation, of the indigenous, Islam and Christian terms is effective for the writer’s purpose. Thus, the writer’s choice was suitable in his effort to communicate the original teaching.Contribution: This study contributes to inter-religious communication by identifying the Javanese indigenous communication pattern, particularly the placement of their messages inside their poem’s structure and in various terminologies. Strengthening inter-religious communication to create a mutual understanding in Indonesian pluralistic society is needed especially as the Javanese indigenous religions are often misunderstood.